A multi-centred sequential trial comparing PEGASUS, an intervention to promote shared decision making about breast reconstruction with usual care. Issue 4 (April 2022) - Paraskeva, N.; Tollow, P.; Clarke, A.; White, P.; Powell, J.E.; Cox, D.M.; Harcourt, D.M.
Summary: Decision making about breast reconstruction (BR) is complex. The Patients' Expectations and Goals: Assisting Shared Understanding of Surgery (PEGASUS) intervention aims to support shared decision making by helping women and clinicians clarify and discuss their expectations around reconstructive surgery. We conducted a multi-centred sequential trial comparing PEGASUS ( n  = 52) with usual care (UC) ( n  = 86) in women considering reconstruction, who completed outcome measures at baseline, and 3, 6 and 12 months post-surgery. The primary outcome was BR-specific quality of life (Breast-Q) 6 months post-intervention. Secondary outcomes were health-related quality of life (EQ-5D-5L), capabilities (ICECAP-A) and decisional regret, compared using t -tests and Cohen's d . Comparative analyses revealed no significant differences between groups in Breast-Q scores at any time point, except for a favourable effect for UC on psychological well-being at 3 months ( t  = -2.41, p = .019, d = -0.59). Intervention participants reported significantly higher, therefore improved, ICECAP-A ( t  = -2.13, p = .037, d  = -0.45) and EQ VAS ( t  = -2.28, p = .026, d  = -0.49) scores at 12 months compared to UC. Decisional regret was significantly lower in the PEGASUS group compared to the UC group at 6 months ( t =2.06, p = . 044, d = -0.51), but this was not sustained at 12 months. In conclusion, the PEGASUS intervention offers some benefits to women considering BR. At times, women experienced less decisional regret, improved health-related quality of life and capability well-being. Findings are discussed in the light of fidelity testing and embedding PEGASUS into practice.